Viscosity Reduction of Sharqi Baghdad Heavy Crude Oil Using Different Polar Hydrocarbons, Oxygenated Solvents - Qasim Hussein, Hussein; Abdul-wahhab Mohammad, Saja (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
This work studied the facilitation of the transportation of Sharqi Baghdad heavy crude oil characterized with high viscosity 51.6 cSt at 40 °C, low API 18.8, and high asphaltenes content 7.1 wt.%, by reducing its viscosity from break down asphaltene agglomerates using different types of hydrocarbon and oxygenated polar solvents such as toluene, methanol, mix xylenes, and reformate. The best results are obtained by using methanol because it owns a high efficiency to reduce viscosity of crude oil to 21.1 cSt at 40 °C. Toluene, xylenes and reformate decreased viscosity to 25.3, 27.5 and 28,4 cSt at 40 °C, respectively. Asphaltenes content decreased to 4.2 wt. % by using toluene at 110 °C. And best improvement in API of the heavy crude oil is 26.1 at 40 °C by using xylenes.